EVALUATION OF SPECIFIC HEAVY METALS IN DRINKING WATER CONSUMED IN YAR’AKWA QUARTERS, NA’IBAWA, TARAUNI LGA, KANO STATE, NIGERIA - Mujahid, Sulaiman Nasir; Bala, Muhammad Umar; Isyaku, Adam Mubarak; Abba, Musa; Sani, Suleiman; Aliyu, Hussaini; Muhammad, Aliyu; Jamilu, Yahuza; Shafiu, Sani; Umar, Musa Yusuf (FUDMA JOURNAL OF SCIENCES, 2024)
The study focused on analyzing selected heavy metals in drinking water used in Yar’akwa Quarters. Water samples were collected from boreholes, taps, and wells across different locations and times. Using Atomic Absorption Spectrophotometry (PerkinElmer PinAAcle 900h AAS), the samples were tested for Ni, Pb, Co, Zn, and Cu. Results showed that Lead (Pb) was not detected in any samples. Cobalt concentrations ranged from 0.032 to 0.050 mg/L, with a maximum of 0.050 mg/L, while copper ranged from 0.040 to 0.057 mg/L, peaking at 0.057 mg/L. Nickel levels ranged from 0.026 to 0.052 mg/L, with a maximum of 0.052 mg/L, and zinc ranged from 0.020 to 0.027 mg/L, reaching up to 0.027 mg/L, all observed in the Na’ibawa borehole water sample. These values conform to World Health Organization (WHO 2020) standards, suggesting that the water in this area is suitable for drinking, domestic, and other purposes. However, ensuring ongoing monitoring of boreholes and tap water sources is recommended.